1993
DOI: 10.1016/0022-3468(93)90692-e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the right atrial venous oxygen saturation as a physiologic monitor in a neonatal model

Abstract: Pulmonary artery (PA) mixed venous saturation (SvO2) has become a crucial monitor in the adult intensive care unit, but is not used in neonates because of the difficulty in PA catheterization. We evaluated the possibility of utilizing the right atrial venous oxygen saturation (RAvO2), which is easily accessed in the neonate, as a monitor of the effects of mechanical ventilation and intravascular volume in an animal model selected to be the size of the human neonate. A continuous RAvO2 monitoring catheter was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Despite studies questioning the value of SvO 2 in treating ICU patients [45, [53][54][55], considerable evidence suggests that ScvO 2 has a beneficial role in the early management of critically ill patients and even neonates [25,56]. The ability to access this information earlier in the phases of critical illness is now a reality and further studies are now in progress to confirm that early recognition and treatment of deranged ScvO 2 values have significant outcome benefit.…”
Section: Limitations and Future Questionsmentioning
confidence: 98%
“…Despite studies questioning the value of SvO 2 in treating ICU patients [45, [53][54][55], considerable evidence suggests that ScvO 2 has a beneficial role in the early management of critically ill patients and even neonates [25,56]. The ability to access this information earlier in the phases of critical illness is now a reality and further studies are now in progress to confirm that early recognition and treatment of deranged ScvO 2 values have significant outcome benefit.…”
Section: Limitations and Future Questionsmentioning
confidence: 98%
“…Several studies report a significant increase in ScvO 2 following volume loading both in animals 11–14 and in humans 1,2 . The increase in ScvO 2 was associated with an increase in cardiac output and in oxygen delivery to tissues 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Pearse et al 6 evaluated changes in ScvO 2 following major surgery and found that tissues' oxygen consumption is an important determinant of ScvO 2 Second, this study was based on spot in vitro measurements of ScvO 2 . Several authors have used central venous fiberoptic oxygen saturation catheters to assess the clinical usefulness of ScvO 2 4,7,10,13 . These catheters provided an accurate continuous monitoring of central venous oxygen saturation, a large number of measurements and a close tracking of ScvO 2 changes across a wide range of hemodynamic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] It is also used for monitoring the response to therapy and for follow-up of infants with patent ductus arteriosus. In neonatal intensive care units, umbilical arterial and venous catheters are used frequently either to monitor blood pressure or to administer medication and parenteral nutrition.…”
Section: Enous Oxygen Can Be Measured As Anmentioning
confidence: 99%